Deterritorialising media:resilience and activism - Carlson, Bronwyn; Browning, Daniel; Finlay, Summer May; Clarke, Allan; Husband, Dale (Communication Research and Practice, 2018)
ANZCA2017 opened with an Indigenous media plenary session, marking the anniversary of the 1967 referendum which voted to amend discriminatory references to Indigenous people in the Australian Constitution, and the 10th anniversary of National Indigenous Television (NITV). Deterritorialising Media: resilience and Activism explored key changes to Indigenous media practice and publishing over the last decade. Chair Professor Bronwyn Carlson, Head of Indigenous Studies at Macquarie University was joined by media practitioners from Australia and Aotearoa/New Zealand and this article is an edited transcript of their discussion.